Analysis of the Cycle Selling Skill System in Increasing Sales of Health Insurance Products - Putri, Khairani; Lestari, Annio Indah; Jannah, Nurul (Ilomata International Journal of Management, 2024)
In this context, the sale of health insurance products is an important factor for insurance companies to meet the needs of a growing market. Insurance companies need to develop effective sales skills. This research aims to provide a better understanding of the sales skills required in the health insurance industry, as well as to identify effective strategies and solutions in increasing sales of health insurance products. The research method used in this study is a qualitative approach. By relying on data collected from observations, interviews and documentation, the results of this study explain that the implementation of the cycle selling skill system at PT Chubb Life Insurance Indonesia Medan has provided positive results in increasing sales of health insurance products. However, this success requires continuous efforts in agent training, use of technology, and product innovation to face existing challenges and maximize sales opportunities, insurance agents can increase health insurance sales more effectively. The stages in this analysis help insurance agents understand the needs of potential customers, provide appropriate solutions, and handle objections that may arise.